Analisis Kemampuan Membaca Permulaan Siswa Kelas II Dengan Teknik Asesmen Literasi Awal/ Early Grade Reading Asessment - Anggun Ria Ignasis Munthe; Febrina Dafit (NUSANTARA: Jurnal Inovasi Pendidikan, 2026)
This study aims to describe the early reading ability of second-grade students using the Early Grade Reading Assessment  technique. The research employed a naturalistic inquiry method with a qualitative approach. The subjects of the study were 27 second-grade students. Data were collected through two EGRA test stages: the first stage involved naming the alphabet within 60 seconds, and the second stage involved reading meaningful words within 60 seconds. Data validity was ensured through source triangulation and technique triangulation. Data analysis was conducted using percentage analysis and the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that students’ ability to name alphabet letters was in the high category, with 23 students (85%) able to correctly name all 26 letters within 60 seconds (100%), while 4 students (15%) named 24 letters with a 92.30% accuracy rate. In the meaningful word reading test, 20 students (74%) read 20 words correctly within 60 seconds (high category), 5 students (18%) achieved 95% accuracy (high category), 1 student (4%) was in the moderate category (75%), and 1 student (4%) was in the low category (0%). Overall, the findings indicate that the students’ early reading ability is categorized as high, although a small number of students still require additional guidance to improve their reading accuracy and speed.